Study on adolescents’ attitudes and attachment toward companion animals: mitigating the negative effects of cultural estrangement on wellbeing - Koyasu, Hikari; Ogasawara, Sakura; Kikusui, Takefumi; Murai, Toshiya; Nishida, Atsushi; Nagasawa, Miho (Frontiers in Psychology, 2025)
The mental health of adolescents is an important issue, since it has a significant impact on their future lives. In this regard, one of the methods for supporting adolescents’ mental health is the interaction with companion animals, which is becoming widely recognized. In our previous research, we showed that owning companion animals has positive effects on adolescents’ wellbeing and cultural estrangement. However, the effect was notably small. The findings of studies examining companion animals and mental health are inconsistent. These results suggest the need to not only focus on pet ownership, but also how their relationship with companion animals such as attitudes toward animals and attachment. In addition, the impact of cultural estrangement on wellbeing is not always negative, and their relationship may not be a simple correlation. Therefore, this study focused on individuals with high cultural estrangement and aimed to clarify how attitudes toward animals and attachment to their pets differ depending on whether their wellbeing is high or low. Based on the results, the group with high cultural estrangement and high wellbeing exhibited an anthropocentric attitude and a strong interest in nature and ecology. In addition, the group with high cultural estrangement and high wellbeing exhibited close attachment to their pets, which functioned as confidants. This finding highlights the specific role of such animals in supporting adolescents’ mental health during this critical developmental stage.